ANALISIS PENGARUH KINERJA KEUANGAN PERUSAHAAN DENGAN ALAT UKUR EVA, MVA, DAN ROA TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR DI BEJ - Imam Ghozali (Akutansi Bisnis & Manajemen ( ABM ), 2002)
The main purpose of this research was: first of all, tries to analyse the effect of financial performance (EVA, MVA, and ROA) on stock returns of manufacturing companies listed in JSX; secondly, it tries to analyse which among those three analysis tools (EVA, MVA, and ROA) that has the greatest effect on stock returns of the sample companies. The sample in this research was 20 manufacturing companies that were listed in JSX. Those 20 companies were the ones that meet certain research requirement. The observation years were between 1996 to 2000. The technique of analysis was employed in this research is multiple linear regression analysis. The analysis was employed only after a preliminary test which ensured that the data did not violate the classical assumption of normality has been conducted. There were four hypothesis in this research, either partially or simultaneously, that will be tested by using t-test (significant at 10 %, 5 % degree of freedom 98 %), and F-test (significant at 10 %, degree of freedom: 98 %). The result from the first and second research showed that EVA and ROA were not significantly important to the stock return in the partial way in manufacturing companies. The third hypothesis showed that MVA had significant effect on stock return partially, with t-test 10 % and 5 %, df 98 %, was 2,205 with cost significant 0.030. The fourth hypothesis simultaneously that EVA, MVA, and ROA had influenced stock return, with F-test 10 %, df 98 % was 2.338, the value of cost significantly 0.078. The main factors that cause this insignificancy can be categorized as external factors. They may range from the dollar rate fluctuations since 1997, the resignation of President Soeharto in 1998, ethnic conflicts that erupted throughout 1998 - 2000, monetary crisis, company debt restructure